Incumbency advantage of UK members of Parliament 1959 -2010 - Smith, Timothy Edward Hallam (2019)
This thesis provides original quantitative research on MPs’ incumbency advantage in Great Britain from 1959 – 2010. It has been widely agreed since the 1970s that MPs benefit from a small but significant personal vote, such that when they retire, their party receives a penalty in their constituency as a newcomer fights the seat. Much of the empirical work done on incumbency, discussed in the literature review, has been done using individual level data, i.e. asking voters questions about who they vote for and why they do so. This study is based entirely on macro-level data, that of election results. The author felt that whilst voters could provide ex-post facto rationalization or even lies to survey takers about their reasons for voting, election vote counts do not lie. The study adapts two methods of measuring incumbency popular in the US, "slurge" and the "Gelman King Index” for work on Congress, for use in the UK setting.